Mid-Neoproterozoic angular unconformity in the Yangtze Block revisited: Insights from detrital zircon U-Pb age and Hf-O isotopes - Yang, C.; Li, X.; Wang, Xuan-Ce; Lan, Z. (Elsevier, 2015)
Middle Neoproterozoic sedimentary rocks are widespread in the South China Block, especially around the periphery of the Yangtze Block. They are separated into the Sibao and Danzhou groups (and their equivalents) by a “mid-Neoproterozoic angular unconformity” in the south margin of the Yangtze Block. This unconformity, previously interpreted as the evidence of continental collision between the Yangtze and Cathaysia blocks, is crucial for understanding the early-middle Neoproterozoic tectonic regime in the South China Block. We report integrated in situ U–Pb, Hf and O isotopes analyses of detrital zircon grains from sandstones across this unconformity, and use these data to decipher their sedimentary provenances and shed new light on the basin evolution and the tectonic significance of this mid-Neoproterozoic unconformity.A total of 324 concordant U–Pb zircon analyses are obtained from three sandstone samples, including two from the Yuxi Formation of the Sibao Group and one from the Baizhu Formation of the Danzhou Group that are located below and above the unconformity, respectively. Detrital zircon grains from the lower part of the Yuxi Formation are dominated by a single age population peaked at ca. 830 Ma, providing a maximum depositional age for the formation. Zircon grains from the middle part of the Yuxi Formation and the lowest part of the Baizhu Formation have very similar, “multi-peaked” age patterns, with five distinctive peaks at ca. 840 Ma, ca. 940 Ma, ca. 1620 Ma, ca. 1850 Ma and ca. 2500 Ma, and zircon grains within the youngest age population are of the similar Hf–O isotopic features in the two samples, indicating that sediments across the mid-Neoproterozoic unconformity share similar sedimentary provenances and deposited within the similar tectonic setting. Appearance of abundant low-δ18O magmatic zircon grains from these sediments is coincident with regional intraplate anorogenic magmatism at ca. 850 Ma, suggesting that both the Sibao and Danzhou groups were most likely deposited in a continental rift basin. Thus, this study strongly argues against the orogenic origin of the regional mid-Neoproterozoic unconformity between them. Our new data suggest that the mid-Neoproterozoic unconformity is likely attributed to a rapid regional crust uplifting (associated with widespread mafic and granitic magmatism), unroofing and basin subsidence related to the proposed mantle plume activity at ca. 825 Ma.